Posouzení informačního systému u vybrané firmy a návrh změn - Méheš, Filip (Vysoké učení technické v Brně. Ústav soudního inženýrství)
Dipomová práca obsahuje vysvetlenie základných pojmov a princípov využívaných v problematike informačných systémov. Súčasťou práce sú analýzy súčasného stavu informačného systému vo vybranej firme a posúdenie jeho efektívnosti. Na základe týchto analýz je navrhnutý súbor riešení na zlepšenie súčasného stavu a elimináciu rizík z hľadiska vyváženosti a efektívnosti informačného systému.

The diploma thesis contains a clarification of the fundamental notions and the principles utilized in the informational systems issues. The analysis of the contemporary condition of the information system applied in a particular company and the evaluation of its effectiveness are the essential parts of the thesis. On the basis of these analyzes, a set of solutions is designed to improve present conditions and eliminate the risks, in terms of stability and effectiveness of the information system.
Information System Assessment and Proposal for ICT Modification
Keywords: Informačný systém; dáta; analýza; efektívnosť; riziko; Zefis; HOS 8.; Information system; data; analysis; efficiency; risk; Zefis; HOS 8.